2020
DOI: 10.3390/ijms21020477
|View full text |Cite
|
Sign up to set email alerts
|

Blood Co-Circulating Extracellular microRNAs and Immune Cell Subsets Associate with Type 1 Diabetes Severity

Abstract: Immune cell subsets and microRNAs have been independently proposed as type 1 diabetes (T1D) diagnostic and/or prognostic biomarkers. Here, we aimed to analyze the relationships between peripheral blood circulating immune cell subsets, plasmatic microRNAs, and T1D. Blood samples were obtained from both children with T1D at diagnosis and age-sex matched healthy controls. Then, immunophenotype assessed by flow cytometry was coupled with the quantification of 60 plasmatic microRNAs by quantitative RT-PCR. The asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 66 publications
(81 reference statements)
3
24
1
Order By: Relevance
“…Another study analyzed plasma miRNAs, immune cell subsets, and specific features of T1D and revealed correlations between miRNAs and T1D onset (let7c-5p, let7d-5p, let7f-5p, let7i-5p, miR146a-5p, miR423-3p, miR423-5p), C-peptide levels in the serum (miR142-5p, miR29c-3p), glycated hemoglobin (miR26a-5p, miR223-3p), and ketoacidosis (miR29c-3p). Furthermore, the analysis pointed towards a link between plasma miRNAs and certain immune cell subsets, which was limited to T1D patients (87). In diabetic NOD mice, miR409-3p was reduced in the plasma as well as in islet infiltrates, and miR409-3p levels were associated with insulitis severity.…”
Section: Cell-free Circulating Mirnasmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study analyzed plasma miRNAs, immune cell subsets, and specific features of T1D and revealed correlations between miRNAs and T1D onset (let7c-5p, let7d-5p, let7f-5p, let7i-5p, miR146a-5p, miR423-3p, miR423-5p), C-peptide levels in the serum (miR142-5p, miR29c-3p), glycated hemoglobin (miR26a-5p, miR223-3p), and ketoacidosis (miR29c-3p). Furthermore, the analysis pointed towards a link between plasma miRNAs and certain immune cell subsets, which was limited to T1D patients (87). In diabetic NOD mice, miR409-3p was reduced in the plasma as well as in islet infiltrates, and miR409-3p levels were associated with insulitis severity.…”
Section: Cell-free Circulating Mirnasmentioning
confidence: 98%
“…Based on the high numbers of miRNAs and their involvement in virtually all biological processes, including immune regulation, multiple studies investigated their biomarker potential in the context of islet autoimmunity and T1D (42,56,66,(85)(86)(87)(88)(89)(90)(91). In contrast to the majority of disease symptoms, biomarkers enable the objectively quantifiable characterization of a disease and its progression.…”
Section: Mirnas As Biomarkers For Islet Autoimmunity and T1dmentioning
confidence: 99%
“…miRNAs are also present in body fluids, such as blood, urine and cerebrospinal fluid [ 29 ], showing stability dictated possibly by their association with either vesicular structures as the extracellular vesicles (EVs) or associated with RNA-binding proteins (Argonaute2 [Ago2]) or lipoprotein complexes (high-density lipoprotein [HDL]) [ 30 ].…”
Section: Mirnas Landscape and General Characteristicsmentioning
confidence: 99%
“…Asymptomatic carotid stenosis [63], familial hypercholesterolemia and coronary artery disease [64], angina pectoris [65], ischemic dilated cardiomyopathy [66], small and large abdominal aortic aneurysm [61], myocardial ischemia/reperfusion [67,68], diabetes mellitus [14,24,52,54] hsa-miR-26a-5p 3p22.2 12q14.1 [69] Heart failure, cardiac hypertrophy [70], myocardial infarction [51,71,72], ischemia/reperfusion injury [73], pulmonary arterial hypertension [74], T1DM [75], diabetic nephropathy [57] hsa-miR-29a-3p 7q32.3…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial aneurysms [111], coronary heart disease [112], myocardial infarction [113], myocardial hypertrophy [114], dilated cardiomyopathy [115], pulmonary arterial hypertension [116], acute ischemic stroke [89], ascending aortic aneurysm [49] hsa-miR-145-5p 5q33 Hypertension [117,118], dilated cardiomyopathy [119], myocardial infarction [120,121], stroke [121], acute cerebral ischemic/reperfusion [122], T2DM [24,123], T1DM [52], diabetic retinopathy [124], gestational diabetes mellitus [125] hsa-miR-146a-5p 5q33.3 [126,127] Angiogenesis [128], hypoxia, ischemia/reperfusion-induced cardiac injury [129], myocardial infarction [17], coronary atherosclerosis, coronary heart disease in patients with subclinical hypothyroidism [130], acute ischemic stroke, acute cerebral ischemia [131], T2DM [24,52], T1DM [75], diabetic nephropathy [57] hsa-miR-181a-5p 1q32.1 9q33.3 [132] Regulation of hypertension-related genes [50], atherosclerosis [132], metabolic syndrome, coronary artery disease [133], non-alcoholic fatty liver disease [134], ischaemic stroke, transient ischaemic attack, acute myocardial infarction [135,136], obesity and insulin resistance [62,…”
Section: Introductionmentioning
confidence: 99%